Cultivating Sustainability: Principal Leadership Perspectives on School Food Gardens in South Africa - Kathija Yassim; Mukateko Louisa Sithole (Managere: Indonesian Journal of Educational Management, 2026)
School food gardens are increasingly recognized as valuable contexts for Education for Sustainability (EfS), yet limited research has examined the leadership practices that enable their pedagogical integration. This study explored how primary school principals perceive and utilize food gardens as third learning spaces that support sustainability-oriented education. A qualitative case study design within an interpretive paradigm was employed. Data were collected through semi-structured interviews with six primary school principals whose schools had established food gardens embedded in teaching and learning programs. Data were analyzed using Tesch’s eight-step coding procedure. Findings indicate that school food gardens extend beyond food production and nutrition support, functioning as experiential learning environments that foster teacher professional learning, enhance learner self-efficacy, and promote sustainability literacy. Principals played a central role in enabling these outcomes by articulating a shared vision, safeguarding instructional time, facilitating professional development, and building collaborative networks among teachers, learners, families, and community stakeholders. The study shows that the effectiveness of school food gardens depends not only on their physical presence but also on leadership processes that integrate them into the school’s pedagogical mission. The implications suggest that educational leadership programs should strengthen principals’ instructional leadership skills to integrate sustainability initiatives into curriculum practice better. Education authorities are encouraged to institutionalize school food gardens as structured learning infrastructure, supported by teacher training, community engagement, and protected instructional time, to ensure sustained educational impact.